Indications, contraindications, and clinical significance of Holter monitoring device - Abdullah, Marwah Yakoop; Zarei, Traad L.; Althaidy, Mubarak M.; Alghamdi, Ibrahim A.; Alkindy, Abdulrhman S.; Almalki, Ibrahim H.; Barnawi, Jomannah F.; Alfayez, Eman H.; Alali, Amjad S.; Merza, Saleh F.; Hasan, Fatema S.; Almaghrabi, Saad K. (International Journal Of Community Medicine And Public Health, 2022)
Holter electrocardiogram monitoring devices are mainly indicated to assess the 24-hour heart rate and rhythm, enabling clinicians and physicians to evaluate the underlying disorders, possibly arrhythmias. The clinical significance of these modalities was apparent in different clinical events, including cardiac and non-cardiac ones. Many applications and clinical advantages were reported since the device was first reported, which changed the way how healthcare settings deal with and monitor cardiac rhythm and associated abnormalities. Evidence shows that Holter monitoring devices are useful in the appropriate patient populace and are very efficacious in diagnosing and following cardiac arrhythmias and other different cardiac conditions, which can significantly enhance the prognosis and management of cardiovascular patients. In this context, it has been shown that primary healthcare physicians should always be aware that many patients might be present with asymptomatic cardiac arrhythmias. However, not many studies have adequately assessed them in the non-cardiac population, which calls for conducting more future investigations. In the present literature review study, we aim to discuss the indications, contraindications, and clinical significance of using the Holter monitoring device based on data from the relevant studies in the literature.